Purification and characterization of two cysteine peptidases of the Mediterranean fruit fly Ceratitis capitata during metamorphosis - Rabossi, Alejandro (2008)
In holometabolous insects, there is a complete body remodeling from larva to adult. We determined in Ceratitis capitata that the transition from pre-pupa to pupa, 40 to 48 h after puparium formation (h APF), is a key moment of metamorphosis; when salivary glands, intestine, fat body, and muscles are in different stages of cell death. At 44-46 h APF, muscles from segments 1-3 (thoracic region) appeared fully disintegrated, whereas posterior muscles just started death processes. To understand some of the biochemical events eventually involved in histolytic processes during early metamorphosis, two cysteine peptidases coined "Metamorphosis Associated Cysteine Peptidase" (MACP-I and MACP-II) were purified to homogeneity from 40-46-h APF insects. Both enzymes were inhibited by Ep-475, a specific inhibitor of papain-like cysteine-peptidases. MACP-I is a single chain protein with an apparent molecular mass of 80 kDa and includes several isoforms with pI values of pH 6.25-6.35, 6.7, and 7.2. The enzyme has an optimum pH of 5.0 and its pH stability ranges from pH 4.0 to 6.0. The molecular weight and N-terminal sequence suggest that MACP-I might be a novel enzyme. MACP-II is an acidic single chain protein with a pI of pH 5.85 and an apparent molecular mass of 30 kDa. The enzyme is labile with a maximum stability in the pH range of 4.0 to 6.0 and an optimum pH among 5.0 to 6.0. MAPCP-II characteristics suggest it is a cathepsin B-like enzyme